Pipkin type III fractures: a narrative review of literature and comparative opinion on ORIF vs. arthroplasty - Shakya, Sujan; Zhang, Qing; Wen, Yi; Wen, Xinag; Cheng, Long (Frontiers in Surgery, 2025)
Pipkin Type III is extremely rare and is associated with worse prognosis and several complications. There is still no consensus on the management of injuries and whether these fractures should be treated surgically with ORIF or arthroplasty. Pipkin type III involves a combination of ipsilateral femoral head and neck fractures. Physioanatomical complexity of this fracture is often challenging, with a poorer prognosis than any other subgroups. The most common complications after management of Pipkin Type III are avascular necrosis of the femoral head and post-traumatic osteoarthritis. The treatment modality with open reduction and internal fixation (ORIF) or total hip arthroplasty (THA) varies according to the severity of the fracture, patient age, time to surgery, and intraoperative findings. Reoperation and surgical intervention pose significant economic burden, functional impairment, and quality of life. This comprehensive review on Pipkin type III demonstrates a throughout exploration of the existing research publications and case studies, focusing on current understanding treatment management strategies, outcome associated and decision-making frameworks with algorithms for decision schemes. By incorporating additional references of our institutional experiences, it aims to expand the current body of knowledge on Pipkin III fractures, offering fresh perspectives and crucial insights for surgeons in decision-making processes.